ANALISIS KELAYAKAN BISNIS DITINJAU DARI ASPEK KEUANGAN PRODUK EKONOMI KREATIF (Studi Kasus Pada PKM-Kewirausahaan “Jadian Yok Cah Malang”) - Ulfatul Munawaroh; Jeni Susyanti; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
This research aimed to describe the results of the business feasibility analysis creative economic products in financial feasibility aspect. This product is a clock that anti dents and unbreakable with design of Malang icon. The case study of this research is Jadian Yok Cah Malang business. The results showed that Break Even Point Rp.36.177.841. or 426 on pieces, Payback Period 2,84 years, Net Present Value Rp. 54.456.233, Profitability Index 2,11, Average Rate of Return 51% and Internal Rate of Return 42%. Based on financial feasibility, Jadian Yok Cah Malang is feasible to be developed.